Deutschmark appreciation and structural change: An overview of economic structural reports - Klaus-Dieter Schmidt (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1997)
Changes in exchange rates have become a prominent issue in Germany and Japan - due to the enormous appreciation of the Deutschmark and the Yen. Conventional wisdom suggests that economic activity will be negatively affected if a currency is going through a phase of appreciation. The paper emphasizes the impact of the strong Deutschmark appreciation on structural change and economic growth in Germany in the 1970s and 1980s. It re-examines the diverging arguments supported in the so-called Structural Reports of the five leading economic research institutes. The paper concentrates on three questions: first, which was the theoretical background of the discussion, second, which were the controversial issues, and third, which could be the lessons for Japan's economic policy drawn from the reports? The author comes to the conclusion that the strong Deutschmark has positively affected the German economy as it has increased the pressure to adjust. However, while manufacturing industries were flexible enough to reduce their staff quickly, service industries were too inflexible to provide relief for the labour market. In this respect, Germany can hardly be a model for Japan. In realizing economic reforms, it has made only little progress.
Keywords: F1; F2; F3; L6; L7; L8; L9; 330; Wechselkurs; Strukturwandel; Kaufkraftparität; Wirtschaftliche Anpassung; Deutschland